Hebraica Catalogers and Cataloging Roles in North America: Today and Tomorrow - Lerner, Heidi (Judaica Librarianship, 2017)
This study looks at current workflows, practices and preparations for the future among North American Hebraica catalogers in academic, government and other special libraries and archives, The survey explores the demographics of the Hebraica cataloging community. Questions were asked about what types of materials this group processes, workplace responsibilities, and metadata practices and trends. The author was very interested to know what steps and types of training Hebraica catalogers are undertaking to learn about new technologies and tools being developed to describe bibliographic and digital resources.